2020
DOI: 10.1002/jmv.25688
|View full text |Cite
|
Sign up to set email alerts
|

The 2019‐new coronavirus epidemic: Evidence for virus evolution

Abstract: There is a worldwide concern about the new coronavirus 2019-nCoV as a global public health threat. In this article, we provide a preliminary evolutionary and molecular epidemiological analysis of this new virus. A phylogenetic tree has been built using the 15 available whole genome sequences of 2019-nCoV, 12 whole genome sequences of 2019-nCoV, and 12 highly similar whole genome sequences available in gene bank (five from the severe acute respiratory syndrome, two from Middle East respiratory syndrome, and fiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
401
1
42

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 582 publications
(454 citation statements)
references
References 20 publications
10
401
1
42
Order By: Relevance
“…Such changes thus have the potential to lead to variants that have high pathogenic potential when transmitted to humans [29][30][31]. Recently, two mutations of the S protein and N protein SARS-CoV-2 may explain its zoonotic transmission [32]. Genomic alignment of 54 SARS-CoV-2 genomes identified two hotspots of hypervariability at positions 8789 (synonymous variant) and 28,151(Ser/ Leu change), located in the polyprotein and ORF8 genes respectively [33].…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Such changes thus have the potential to lead to variants that have high pathogenic potential when transmitted to humans [29][30][31]. Recently, two mutations of the S protein and N protein SARS-CoV-2 may explain its zoonotic transmission [32]. Genomic alignment of 54 SARS-CoV-2 genomes identified two hotspots of hypervariability at positions 8789 (synonymous variant) and 28,151(Ser/ Leu change), located in the polyprotein and ORF8 genes respectively [33].…”
Section: Genetic Diversitymentioning
confidence: 99%
“…The previous findings suggest that SARS-CoV-2 is a new virus that is distinct from SARS-CoV and MERS-CoV but most probably originated in bats, similar to SARS-CoV and MERS-CoV [42]. Another recent study confirmed that SARS-CoV-2 significantly clustered with a sequence from the bat SARS-like CoV that was isolated in 2015 [76]. However, the existence of an intermediate host for SARS-CoV-2 is still not verified (Figure 2).…”
Section: Sars-cov Mers-cov and The Newly Discovered Sars-cov-2: Simmentioning
confidence: 87%
“…Phylogenetic analysis of the complete viral genome revealed that the coronavirus was most closely related (89.1% nucleotide similarity) to a group of SARS-like coronaviruses previously sampled from bats in China. Benvenuto et al built a phylogenetic tree in-cluding the whole-genome sequences of SARS-CoV-2 and highly similar available whole-genome sequences in GenBank [9] . The phylogenetic tree showed that SARS-CoV-2 clustered with a bat SARS-like coronavirus sequence isolated in 2015, whilst fast unconstrained Bayesian approximation (FUBAR) analysis revealed mutations in the spike glycoprotein and nucleocapsid protein.…”
Section: Potential Hostsmentioning
confidence: 99%